Carbon-coated lithium iron manganese phosphate positive electrode material, preparation method thereof and application of carbon-coated lithium iron manganese phosphate positive electrode material in lithium ion battery

The carbon-coated lithium manganese iron phosphate positive electrode material is prepared by microwave hydrothermal combined annealing, which solves the problems of low conductivity and low lithium ion diffusion coefficient of existing materials, and achieves efficient electrochemical performance, including excellent cycling stability and high magnification capacity.

CN120081350APending Publication Date: 2025-06-03CENT SOUTH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510176153.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-06-03

AI Technical Summary

Technical Problem

The existing lithium manganese iron phosphate positive electrode materials have low conductivity and low lithium ion diffusion coefficient, which makes it difficult to exert the theoretical specific capacity of the material and poor cycle stability and rate performance.

Method used

The carbon-coated lithium manganese iron phosphate positive electrode material is prepared by microwave hydrothermal bonding annealing to achieve the formation of a nanorod-like structure and improve the crystallinity and electrochemical properties of the material.

Benefits of technology

The material has a small particle size and uniform distribution, high crystallinity, and uniform surface carbon coating, showing excellent electrochemical properties, including excellent cycling stability and high magnification capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120081350A_ABST
    Figure CN120081350A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon-coated lithium iron manganese phosphate positive electrode material, a preparation method thereof and application of the carbon-coated lithium iron manganese phosphate positive electrode material in a lithium ion battery, and belongs to the technical field of lithium ion batteries. The preparation method comprises the following steps: uniformly mixing a lithium source, a phosphorus source, a manganese source, an iron source and an organic carbon source in water, adjusting the pH value to form a mixed solution, carrying out a hydrothermal reaction on the mixed solution under microwave heating, and carrying out freeze drying and annealing on a hydrothermal reaction product to obtain the carbon-coated lithium iron manganese phosphate positive electrode material. The preparation method has the advantages that the preparation process is simple, large-scale production is met, and the obtained lithium manganese iron phosphate material is high in crystallinity, has a nanorod-like structure, is uniformly and compactly coated with surface carbon, shows excellent electrochemical performance, and has excellent cycling stability and high rate capacity when being applied to a lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a cathode material for lithium-ion batteries, specifically to a carbon-coated lithium iron manganese phosphate cathode material, and also to a preparation method of the carbon-coated lithium iron manganese phosphate cathode material and the application of the carbon-coated lithium iron manganese phosphate cathode material in lithium-ion batteries, belonging to the technical field of lithium-ion batteries. Background Art

[0002] With the rapid development of the new energy field, the demand for high-performance lithium-ion batteries is increasing day by day, and the cathode material is a key factor restricting the development of high-performance lithium-ion batteries.

[0003] The olivine-structured lithium iron phosphate cathode material gradually occupies a dominant position in the market due to its high safety performance, long cycle life, environmental friendliness, low price and other advantages. The working voltage of lithium iron phosphate is relatively low (3.45V vs. Li + / Li), resulting in the battery energy density being unable to meet the growing usage requirements of people. Lithium iron manganese phosphate has a higher working voltage and energy density compared to lithium iron phosphate, and is widely regarded as a very promising upgraded alternative material for lithium iron phosphate. However, the intrinsic defects of low conductivity and low lithium ion diffusion coefficient of lithium iron manganese phosphate materials make it difficult to achieve the theoretical specific capacity of the material. During the electrochemical reaction process of lithium iron manganese phosphate batteries, the dissolution and precipitation of Mn 3+ and the Jahn-taller effect lead to poor cycle stability and rate performance of the material.

[0004] The most common synthesis methods of lithium iron manganese phosphate cathode materials mainly include solid-phase methods and liquid-phase methods. Solid-phase methods mainly include high-temperature solid-phase methods and carbothermal reduction methods, etc. These methods have high energy consumption and are difficult to achieve uniform mixing of manganese and iron, resulting in poor electrical properties. The liquid-phase method can well achieve uniform mixing of raw material molecules at the molecular level, and can effectively control the growth and aggregation of particles, producing particles with smaller particle size and more uniform distribution. For example, Chinese Patent (Publication No.: CN118198328A) discloses a carbon-coated lithium iron manganese phosphate composite material and its preparation method. It obtains lithium iron manganese phosphate particles through hydrothermal method and calcination, and then coats carbon nanotubes on the surface of the lithium iron manganese phosphate particles by spraying. Finally, a carbon-coated lithium iron manganese phosphate composite material is obtained, the core of which is a lithium iron manganese phosphate material with the chemical formula LiMn x Fe y PO 4, where 0.3 ≤ x ≤ 0.7, 0.3 ≤ y ≤ 0.7, and x + y = 1; the core-shell is a carbon nanotube coating layer composite with isomeric polypyridine; the particle size of the core material is 100 - 600 nm, and the thickness of the outer coating layer is 0.5 - 10 nm. This method prepares lithium iron phosphate manganese by hydrothermal method, which has a long hydrothermal reaction time, the obtained material has low crystallinity, uneven particle size, and requires an additional carbon coating process. The process is complex and the production efficiency is low. Summary of the Invention

[0005] Based on the above technical problems existing in the prior art, the first object of the present invention is to provide a carbon-coated lithium iron phosphate manganese cathode material, which has a nanorod-like structure, small and uniform particle size, high crystallinity, and uniform surface carbon coating, showing excellent electrochemical performance.

[0006] The second object of the present invention is to provide a preparation method of a carbon-coated lithium iron phosphate manganese cathode material. This method is completed by one-step microwave hydrothermal combined with annealing. Its process is simple, time-consuming is short, energy consumption is low, it meets large-scale production, and the prepared material has advantages such as controllable particle size, high purity, good crystallinity, and less agglomeration.

[0007] The third object of the present invention is to provide an application of a carbon-coated lithium iron phosphate manganese cathode material. When it is applied to a lithium ion battery, it has excellent cycle stability and high rate capacity.

[0008] To achieve the above technical objectives, the present invention provides a preparation method of a carbon-coated lithium iron phosphate manganese cathode material. In this method, a lithium source, a phosphorus source, a manganese source, an iron source, and an organic carbon source are mixed uniformly in water, and then hydrothermal reaction is carried out under microwave heating. The hydrothermal reaction product is freeze-dried and annealed to obtain the carbon-coated lithium iron phosphate manganese cathode material.

[0009] The key to the preparation method of the carbon-coated lithium iron manganese phosphate material proposed by the present invention lies in carrying out a hydrothermal reaction by microwave heating to achieve the efficient synthesis of the precursor of the carbon-coated lithium iron manganese phosphate material. Under the action of microwave heating, not only can the elemental components such as manganese and iron be uniformly mixed at the atomic level, making the internal volume change of the lithium iron manganese phosphate material generated by the reaction highly consistent, improving the structural stability of the lithium iron manganese phosphate material, but also microwave heating has the characteristics of uniformity and fast rate, enabling the rapid and uniform nucleation of the lithium iron manganese phosphate material, which is conducive to obtaining crystal nuclei with small particle size and uniform distribution. At the same time, it is conducive to the rapid growth of crystal nuclei to form a nano-scale lithium iron manganese phosphate material with high crystallinity. The organic carbon source adsorbs on the surface of the lithium iron manganese phosphate crystal nuclei, which can affect the growth of the crystal nuclei and is conducive to obtaining a lithium iron manganese phosphate material with a nanorod-like structure. This nanorod-like structure can reduce the migration resistance of lithium ions and achieve their rapid insertion and extraction. The organic carbon source adsorbed on the surface of the lithium iron manganese phosphate crystal nuclei is in-situ carbonized to form a dense and uniform carbon coating layer, which is beneficial to improving the conductivity of the nano lithium iron manganese phosphate material, increasing its tap density and compaction density. At the same time, the carbon coating layer, as a stable interface layer, reduces the direct contact between the lithium iron manganese phosphate and the electrolyte to inhibit the dissolution of manganese, reduces the polarization degree of the lithium iron manganese phosphate material, and further optimizes its cycle stability and rate performance.

[0010] As a preferred solution, the dosages of the manganese source and the iron source satisfy: molar ratio x = Mn / (Fe + Mn), 0.1 ≤ x ≤ 0.9; the dosage of the phosphorus source satisfies: molar ratio y = (Mn + Fe) / P, 0.98 ≤ y ≤ 1.01; the dosage of the lithium source satisfies: molar ratio z = Li / P, 2.98 ≤ z ≤ 3.01. The lithium source, phosphorus source, manganese source and iron source are proportioned according to the preferred stoichiometric ratio, and the chemical formula of the lithium iron manganese phosphate formed is: LiMn x Fe 1-x PO 4 , 0.1 ≤ x ≤ 0.9. A further preferred solution is that the molar ratio x = Mn / (Fe + Mn), 0.2 ≤ x ≤ 0.8. The most preferred solution is that the molar ratio x = Mn / (Fe + Mn), 0.4 ≤ x ≤ 0.6. Controlling the manganese-iron ratio of the lithium iron manganese phosphate material is crucial for improving its cycle stability and rate performance. When the manganese-iron ratio increases from 0.1 to 0.4 - 0.6, the working voltage of the lithium iron manganese phosphate material increases accordingly, the energy density increases and it has excellent long-cycle stability and rate performance. When the manganese-iron ratio further increases, the rate performance and cycle stability performance of the lithium iron manganese phosphate material deteriorate.

[0011] As a preferred embodiment, the dosage of the carbon source is measured based on the carbon mass content in the carbon-coated lithium iron manganese phosphate cathode material being 2.0% - 8.0%. If the mass ratio of the carbon coating layer on the surface of the carbon-coated lithium iron manganese phosphate cathode material is too low, the formed carbon coating layer is uneven and not dense. If the mass ratio of the carbon coating layer is too high, the coating layer is too thick, which will affect the performance of the material's capacity. Therefore, the dosage of the carbon source is further preferably measured based on the carbon mass content in the carbon-coated lithium iron manganese phosphate cathode material being 4.0% - 6.0%.

[0012] As a more preferred embodiment, the organic carbon source includes at least one of sucrose, glucose, soluble starch, and ascorbic acid. The preferred organic carbon source can affect the morphology of the lithium iron manganese phosphate crystals while serving as a conventional carbon source.

[0013] As a more preferred embodiment, the manganese source includes at least one of manganese nitrate, manganese sulfate, manganese oxalate, manganese nitrate hydrate, manganese sulfate hydrate, and manganese oxalate hydrate.

[0014] As a more preferred embodiment, the iron source includes at least one of ferrous sulfate, ferrous nitrate, ferrous oxalate, ferrous sulfate hydrate, ferrous nitrate hydrate, and ferrous oxalate hydrate.

[0015] As a more preferred embodiment, the lithium source includes at least one of lithium carbonate, lithium oxalate, lithium sulfate, lithium bicarbonate, lithium hydroxide, lithium phosphate, lithium carbonate hydrate, lithium oxalate hydrate, lithium sulfate hydrate, lithium bicarbonate hydrate, lithium hydroxide hydrate, and lithium phosphate hydrate.

[0016] As a more preferred embodiment, the phosphorus source includes at least one of phosphoric acid, ammonium dihydrogen phosphate, lithium phosphate, and lithium dihydrogen phosphate.

[0017] As a more preferred embodiment, the pH is adjusted to 6.0 - 6.5, and the pH value is adjusted using at least one acid-base reagent including lithium hydroxide, phosphoric acid, sulfuric acid, and nitric acid.

[0018] As a preferred embodiment, the conditions for the hydrothermal reaction are as follows: the microwave power is controlled within the range of 400 - 800 W, and the temperature is gradually increased from room temperature to the target temperature of 160 - 230 °C through program control, and the reaction is maintained for 5 - 120 min. Setting a temperature gradient during the microwave hydrothermal reaction can effectively control the nucleation rate and growth rate of the lithium iron manganese phosphate material, thereby obtaining lithium iron manganese phosphate with a relatively uniform particle size distribution and high crystallinity. As a more preferred embodiment, during the process of gradient temperature increase, 1 - 3 temperature gradients are set between room temperature and the target temperature, the holding time for each temperature gradient is 5 - 10 min, and the heating rate is 5 - 15 °C / min. When setting 1 temperature gradient between room temperature and the target temperature during the gradient temperature increase process, for example: heating from room temperature to 80 - 150 °C at a heating rate of 5 - 15 °C / min, holding at this temperature for 5 - 10 min, and then heating to the target temperature of 160 - 230 °C at a heating rate of 5 - 15 °C / min, and reacting at this temperature for 5 - 120 min. When setting 2 temperature gradients between room temperature and the target temperature during the gradient temperature increase process, for example: heating from room temperature to 80 - 100 °C at a heating rate of 5 - 15 °C / min, holding at this temperature for 5 - 10 min, then heating to 140 - 150 °C at a heating rate of 5 - 15 °C / min, reacting at this temperature for 5 - 10 min, and then heating to the target temperature of 160 - 230 °C at a heating rate of 5 - 15 °C / min, and reacting at this temperature for 5 - 120 min.

[0019] As a preferred embodiment, the conditions for the annealing are as follows: the temperature is 600 - 900 °C, and the time is 30 - 180 min. Under the preferred annealing temperature, it is beneficial to improve the carbonization degree of the carbon coating layer and simultaneously improve the crystallinity of the lithium iron manganese phosphate crystal.

[0020] The present invention also provides a carbon-coated lithium iron manganese phosphate cathode material obtained by the above preparation method.

[0021] As a preferred embodiment, it has a core-shell structure, the outer shell is a carbon coating layer, the inner core is nanorod-shaped lithium iron manganese phosphate crystal particles, and the chemical formula of lithium iron manganese phosphate is: LiMn x Fe 1-x PO 4 , 0.1 ≤ x ≤ 0.9.

[0022] As a preferred embodiment, the size distribution of the nanorod-shaped lithium iron manganese phosphate crystal particles is 50 - 250 nm. The 50 - 250 nm nanorod structure can reduce the migration resistance of lithium ions and achieve rapid deintercalation and intercalation.

[0023] The carbon-coated lithium iron manganese phosphate material of the present invention has a uniform and dense carbon coating layer on its surface, which can improve the conductivity of the lithium iron manganese phosphate material. At the same time, as a stable interface layer, it can reduce the direct contact between the lithium iron manganese phosphate material and the electrolyte, thereby inhibiting the dissolution of manganese, reducing the polarization degree of the lithium iron manganese phosphate material, optimizing the cycle stability and rate performance of the lithium iron manganese phosphate material, and the inner core is a lithium iron manganese phosphate material with a nanorod-like structure, which has a nanoscale level, uniform particle size distribution, high crystallinity, good structural stability, and exhibits high electrochemical activity.

[0024] The present invention also provides an application of a carbon-coated lithium iron manganese phosphate cathode material, which is used in a lithium-ion battery.

[0025] Beneficial technical effects brought by the technical solution of the present invention compared with the prior art:

[0026] The grain size of the carbon-coated lithium iron manganese phosphate material of the present invention is 50-250 nm, with uniform distribution, small particle size, and a rod-like structure, which greatly shortens the diffusion path of lithium ions and is beneficial to the insertion and extraction of lithium ions.

[0027] The surface of the carbon-coated lithium iron manganese phosphate material of the present invention has a uniform and dense carbon coating layer, which improves the conductivity of the lithium iron manganese phosphate material, reduces the contact resistance between the lithium iron manganese phosphate material and the electrolyte, effectively reduces the manganese dissolution, improves the structural stability of the lithium iron manganese phosphate material, and enhances the high-rate performance of the material.

[0028] The carbon-coated lithium iron manganese phosphate material of the present invention is applied to a lithium-ion battery, having excellent cycle stability and high-rate capacity.

[0029] The preparation method of the carbon-coated lithium iron manganese phosphate material of the present invention has a simple process flow, short time consumption, low energy consumption, meets large-scale production, and the prepared material has advantages such as controllable particle size, high purity, good crystallinity, and less agglomeration. Description of the Drawings

[0030] Figure 1 XRD patterns of the carbon-coated lithium iron manganese phosphate materials (LMFP / C) prepared in Example 1, Example 2, and Example 3.

[0031] Figure 2 For the carbon-coated lithium iron manganese phosphate material (LiMn 0.5 Mn 0.5 PO 4 / C) prepared in Example 2. SEM image.

[0032] Figure 3 For the carbon-coated lithium iron manganese phosphate material (LiMn 0.5 Mn 0.5 PO 4SEM image of ( / C).

[0033] Figure 4 Rate performance of the carbon-coated lithium iron manganese phosphate materials prepared in Example 2, Example 4, Comparative Example 1 and Comparative Example 2. Detailed implementation manners

[0034] The following specific examples are intended to further illustrate the content of the present invention rather than limit the protection scope of the claims.

[0035] Example 1

[0036] Step (1): Add a certain amount of lithium hydroxide and 5.14 mL of phosphoric acid to 55 mL of deionized water, and magnetically stir at 250 rpm / min for 10 min in an N 2 atmosphere to mix evenly.

[0037] Step (2): Weigh appropriate amounts of manganese sulfate, ferrous sulfate and glucose (the molar ratio of Li: Mn: Fe: P: glucose is 3: 0.6: 0.4: 1: 0.025), add them to the above mixed solution, adjust the pH of the mixed solution to 6.4, and continue to magnetically stir at 250 rpm / min for 15 min in a nitrogen atmosphere.

[0038] Step (3): Transfer the obtained mixed solution to a 100 mL microwave hydrothermal reactor, set a three-stage heating program, and gently and precisely heat it to 100 °C at a heating rate of 10 °C / min and hold for 5 min, then continue to heat to 150 °C and hold for 5 min, and continuously heat until the specified temperature of 180 °C for 30 min. After the reaction is completed, turn on the automatic cooling system to cool to room temperature.

[0039] Step (4): Use a centrifuge to centrifuge and filter to collect the solid product, wash it 4 - 5 times with anaerobic deionized water, and then freeze-dry it in a freeze dryer for 12 h. Then heat the powder in an atmosphere / vacuum tube furnace to 700 °C at a heating rate of 10 °C / min in an N 2 atmosphere and hold for 3 h, take it out after cooling to room temperature to obtain the carbon-coated lithium iron manganese phosphate cathode material.

[0040] Example 2

[0041] Step (1): Add a certain amount of lithium hydroxide and 5.14 mL of phosphoric acid to 55 mL of deionized water, and magnetically stir at 250 rpm / min for 10 min in an N 2 atmosphere to mix evenly.

[0042] Step (2), weigh an appropriate amount of manganese sulfate, ferrous sulfate and glucose (the molar ratio of Li: Mn: Fe: P: glucose is 3: 0.5: 0.5: 1: 0.025), add them to the above-mentioned mixed solution, adjust the pH of the mixed solution to 6.4, and continue to magnetically stir at 250 rpm / min for 15 min under a nitrogen atmosphere.

[0043] Step (3), transfer the obtained mixed solution to a 100 mL microwave hydrothermal reactor, set a three-stage heating program, and gently and precisely heat it to 100 °C at a heating rate of 10 °C / min and keep it warm for 5 min, then continue to heat it to 150 °C and keep it warm for 5 min, and continuously heat it until the specified temperature of 180 °C and react for 30 min. After the reaction is completed, turn on the automatic cooling system to cool to room temperature.

[0044] Step (4), use a centrifuge to centrifuge and filter to collect the solid product and wash it 4-5 times with anaerobic deionized water, and then freeze-dry it in a freeze dryer for 12 h. Then heat the powder in an atmosphere / vacuum tube furnace to 700 °C at a heating rate of 10 °C / min in an N 2 atmosphere and keep it warm for 3 h, take it out after cooling to room temperature, and obtain the lithium iron phosphate cathode material coated with carbon.

[0045] Example 3

[0046] Step (1), add a certain amount of lithium hydroxide and 5.14 mL of phosphoric acid to 55 mL of deionized water, and magnetically stir at 250 rpm / min for 10 min in an N 2 atmosphere to mix them evenly.

[0047] Step (2), weigh an appropriate amount of manganese sulfate, ferrous sulfate and glucose (the molar ratio of Li: Mn: Fe: P: glucose is 3: 0.5: 0.5: 1: 0.025), add them to the above-mentioned mixed solution, adjust the pH of the mixed solution to 6.4, and continue to magnetically stir at 250 rpm / min for 15 min under a nitrogen atmosphere.

[0048] Step (3), transfer the obtained mixed solution to a 100 mL microwave hydrothermal reactor, set a three-stage heating program, and gently and precisely heat it to 100 °C at a heating rate of 8 °C / min and keep it warm for 5 min, then continue to heat it to 150 °C and keep it warm for 5 min, and continuously heat it until the specified temperature of 200 °C and react for 30 min. After the reaction is completed, turn on the automatic cooling system to cool to room temperature.

[0049] Step (4): Use a centrifuge to centrifuge and filter to collect the solid product, wash it 4 - 5 times with anaerobic deionized water, and then freeze - dry it in a freeze - dryer for 12 h. Then heat the powder in an atmosphere / vacuum tube furnace with N 2 atmosphere, at a heating rate of 8 °C / min to 600 °C, hold for 3 h, cool to room temperature and then take it out to obtain the carbon - coated lithium iron manganese phosphate cathode material.

[0050] Example 4

[0051] Step (1): Add a certain amount of lithium hydroxide and 5.14 mL of phosphoric acid to 55 mL of deionized water, and stir magnetically at 250 rpm / min in N 2 atmosphere for 10 min to mix evenly.

[0052] Step (2): Weigh appropriate amounts of manganese sulfate, ferrous sulfate and glucose (the molar ratio of Li:Mn:Fe:P:glucose is 3:0.5:0.5:1:0.025), add them to the above - mentioned mixed solution, adjust the pH of the mixed solution to 6.4, and continue to stir magnetically at 250 rpm / min in a nitrogen atmosphere for 15 min.

[0053] Step (3): Transfer the obtained mixed solution to a 100 - mL microwave hydrothermal reaction kettle, set a three - stage heating program, heat it gently and precisely to 100 °C at a heating rate of 10 °C / min, hold for 5 min, then continue to heat to 150 °C and hold for 5 min, and continue to heat until the specified temperature of 220 °C and react for 30 min. After the reaction is completed, turn on the automatic cooling system to cool to room temperature.

[0054] Step (4): Use a centrifuge to centrifuge and filter to collect the solid product, wash it 4 - 5 times with anaerobic deionized water, and then freeze - dry it in a freeze - dryer for 12 h. Then heat the powder in an atmosphere / vacuum tube furnace with N 2 atmosphere, at a heating rate of 10 °C / min to 700 °C, hold for 3 h, cool to room temperature and then take it out to obtain the carbon - coated lithium iron manganese phosphate cathode material.

[0055] Example 5

[0056] Step (1): Add a certain amount of lithium hydroxide and 5.14 mL of phosphoric acid to 55 mL of deionized water, and stir magnetically at 250 rpm / min in N 2 atmosphere for 10 min to mix evenly.

[0057] Step (2): Weigh an appropriate amount of manganese sulfate, ferrous sulfate, and glucose (the molar ratio of Li:Mn:Fe:P:glucose is 3:0.5:0.5:1:0.025) and add them to the above-mentioned mixed solution. Then adjust the pH of the mixed solution to 6.4, and continue magnetic stirring at 250 rpm / min for 15 min under a nitrogen atmosphere.

[0058] Step (3): Transfer the obtained mixed solution to a 100 mL microwave hydrothermal reactor, set a three-stage heating program, and slowly and precisely heat it to 100 °C at a heating rate of 10 °C / min and keep it warm for 5 min. Then continue heating to 150 °C and keep it warm for 5 min, and continuously heat until the specified temperature of 230 °C and react for 30 min. After the reaction is completed, turn on the automatic cooling system to cool to room temperature.

[0059] Step (4): Use a centrifuge to centrifuge and filter to collect the solid product, and wash it 4 - 5 times with anaerobic deionized water. Then freeze-dry it in a freeze dryer for 12 h. Next, heat the powder in an atmosphere / vacuum tube furnace with N 2 atmosphere at a heating rate of 10 °C / min to 700 °C and keep it warm for 3 h. After cooling to room temperature, take it out to obtain the lithium iron manganese phosphate cathode material coated with carbon.

[0060] Comparative Example 1

[0061] This comparative example provides a preparation method of carbon-coated lithium iron manganese phosphate, and the specific steps are as follows:

[0062] Steps (1) and (2) are the same as those in Example 2 above.

[0063] Step (3): The difference is that the obtained mixed solution is transferred to a 100 mL hydrothermal reactor, and it is slowly heated to 180 °C at a heating rate of 10 °C / min and kept warm for 18 h. After the reaction is completed, it is automatically cooled to room temperature.

[0064] Step (4): Use a centrifuge to centrifuge and filter to collect the solid product, and wash it 4 - 5 times with anaerobic deionized water. Then freeze-dry it in a freeze dryer for 12 h. Next, heat the powder in an atmosphere / vacuum tube furnace with N 2 atmosphere at a heating rate of 10 °C / min to 700 °C and keep it warm for 3 h. After cooling to room temperature, take it out to obtain the lithium iron manganese phosphate cathode material coated with carbon.

[0065] Comparative Example 2

[0066] This comparative example provides a preparation method of carbon-coated lithium iron manganese phosphate, and the specific steps are as follows:

[0067] Steps (1) and (2) are the same as those in Example 2 above.

[0068] Step (3), which is different in that the obtained mixed solution is transferred to a 100 mL hydrothermal reactor, and it is gently heated to 180 °C at a heating rate of 10 °C / min and kept warm for 18 h. After the reaction is completed, it is automatically cooled to room temperature.

[0069] Step (4), using a centrifuge to centrifuge and filter to collect the solid product and washing it 4 - 5 times with anaerobic deionized water, and then freeze-drying it in a freeze dryer for 12 h.

[0070] Step (5), then weighing a certain amount of glucose and ball-milling and mixing it evenly with the above powder, and heating it to 450 °C at a heating rate of 10 °C / min in an atmosphere / vacuum tube furnace under N 2 atmosphere and keeping it warm for 1 h, then continuously heating it to 700 °C and calcining it for 6 h, taking it out after cooling to room temperature, to obtain the carbon-coated lithium iron phosphate manganese cathode material.

[0071] Figure 1 It shows that the carbon-coated lithium iron phosphate manganese materials synthesized in Examples 1 - 3 of the present invention have good crystallinity and purity. The morphology analysis of the carbon-coated lithium iron phosphate manganese materials prepared in Example 2 and Example 4 is as follows Figure 1 and Figure 2 shown. It can be found from the SEM images that the carbon-coated lithium iron phosphate manganese material prepared by the present invention has a nanorod-like morphology, and appropriately increasing the synthesis temperature can make the particle size distribution of the cathode nanomaterials more uniform.

[0072] Application examples

[0073] The carbon-coated lithium iron phosphate manganese nanomaterials obtained in Example 2, Example 4, Comparative Example 1 and Comparative Example 2 of the present invention are respectively made into positive electrode sheets: the above positive electrode materials are uniformly mixed with conductive carbon black and binder PVDF in a ratio of 8:1:1, and NMP is used as a dispersant. The well-mixed positive electrode slurry is uniformly coated on the aluminum foil by an automatic coater, and then transferred to a vacuum drying oven at 100 ℃ and vacuum-dried for 12 h, and then cut into positive electrode sheets with a diameter of 14 mm using a punching machine.

[0074] Using the above electrode sheet as the positive electrode, a lithium sheet as the negative electrode, a 1.0 M LiPF 6 solution of dimethyl carbonate / ethylene carbonate / ethyl methyl carbonate (volume ratio of 1:1:1) containing 5% fluoroethylene carbonate as the electrolyte, and a polypropylene microporous monolayer film as the battery separator, a button cell is assembled in a glove box for battery testing. The obtained test results are as follows.

[0075] As Figure 4As shown, the discharge specific capacities of the carbon-coated lithium iron manganese phosphate material prepared in Example 2 at 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, and 10C are 138.6, 137.3, 137.6, 135.1, 132, 125.8, and 119.5 mAh / g respectively. When returning to 0.1C after high current, the discharge specific capacity is still 135 mAh / g. The discharge specific capacities of the carbon-coated lithium iron manganese phosphate material prepared in Example 4 at 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, and 10C are 138.4, 137.1, 137.5, 134.1, 128.6, 116.2, and 110.6 mAh / g respectively. When returning to 0.1C after high current, the discharge specific capacity is still 134.5 mAh / g. The material in Example 4 has a higher rate discharge specific capacity than that in Example 2, and the discharge specific capacity is also higher when returning to 0.1C after high current, indicating that the material in Example 4 has better rate performance than that in Example 2. Compared with Example 2 and Example 4, the discharge specific capacities of Comparative Example 1 and Comparative Example 2 are greatly reduced, and there is a large difference in rate performance. In summary, it shows that the carbon-coated lithium iron manganese phosphate material synthesized based on the microwave hydrothermal method has excellent electrochemical performance.

[0076] The above are only the preferred embodiments of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the technical principle of the present invention, several improvements and refinements can be made, and these improvements and refinements should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a carbon-coated lithium manganese iron phosphate positive electrode material, characterized in that: After a lithium source, a phosphorus source, a manganese source, an iron source and an organic carbon source are uniformly mixed in water, the pH is adjusted to form a mixed solution, the mixed solution is subjected to a hydrothermal reaction under microwave heating, and the hydrothermal reaction product is freeze-dried and annealed to obtain a carbon-coated lithium manganese iron phosphate positive electrode material.

2. The method for preparing a carbon-coated lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The amounts of the manganese source and the iron source satisfy: molar ratio x=Mn / (Fe+Mn), 0.1≤x≤0.9; and / or, The amount of the phosphorus source satisfies: molar ratio y=(Mn+Fe) / P, 0.98≤y≤1.01; and / or, The amount of the lithium source satisfies: molar ratio z=Li / P, 2.98≤z≤3.01; and / or, The amount of the carbon source is measured based on the carbon mass content of the carbon-coated lithium manganese iron phosphate positive electrode material being 2.0% to 8.0%.

3. The method for preparing a carbon-coated lithium manganese iron phosphate positive electrode material according to claim 1 or 2, characterized in that: The organic carbon source includes at least one of sucrose, glucose, soluble starch and ascorbic acid; and / or, The manganese source includes at least one of manganese nitrate, manganese sulfate, manganese oxalate, manganese nitrate hydrate, manganese sulfate hydrate and manganese oxalate hydrate; and / or, The iron source comprises at least one of ferrous sulfate, ferrous nitrate, ferrous oxalate, ferrous sulfate hydrate, ferrous nitrate hydrate and ferrous oxalate hydrate; and / or, The lithium source includes at least one of lithium carbonate, lithium oxalate, lithium sulfate, lithium bicarbonate, lithium hydroxide, lithium phosphate, lithium carbonate hydrate, lithium oxalate hydrate, lithium sulfate hydrate, lithium bicarbonate hydrate, lithium hydroxide hydrate and lithium phosphate hydrate; and / or, The phosphorus source includes at least one of phosphoric acid, ammonium dihydrogen phosphate, lithium phosphate, and lithium dihydrogen phosphate.

4. The method for preparing a carbon-coated lithium manganese iron phosphate positive electrode material according to claim 1 or 2, characterized in that: The conditions of the hydrothermal reaction are as follows: the microwave power is controlled within the range of 400-800 W, the temperature is increased from room temperature to a target temperature of 160-230° C. by program control, and the reaction is kept at this temperature for 5-120 min.

5. The method for preparing a carbon-coated lithium manganese iron phosphate positive electrode material according to claim 4, characterized in that: During the gradient heating process, 1 to 3 temperature gradients are set between room temperature and the target temperature, the insulation time of each temperature gradient is 5 to 10 minutes, and the heating rate is 5 to 15°C / min.

6. A method for preparing a carbon-coated lithium manganese iron phosphate positive electrode material according to claim 1, 2 or 5, characterized in that: The annealing conditions are: temperature of 600-900° C. and time of 30-180 min.

7. A carbon-coated lithium manganese iron phosphate positive electrode material, characterized in that: Obtained by the preparation method according to any one of claims 1 to 6.

8. The carbon-coated lithium manganese iron phosphate positive electrode material according to claim 7, characterized in that: It has a core-shell structure, with a carbon coating as the outer shell and nanorod-shaped lithium iron manganese phosphate crystal particles as the inner core. The chemical formula of lithium iron manganese phosphate is: LiMn x Fe 1-x PO4, 0.1≤x≤0.

9.

9. The carbon-coated lithium manganese iron phosphate positive electrode material according to claim 8, characterized in that: The size distribution of the nanorod-shaped lithium manganese iron phosphate crystal particles is 50-250 nm.

10. The use of a carbon-coated lithium manganese iron phosphate positive electrode material according to any one of claims 7 to 9, characterized in that: For lithium-ion batteries.

Citation Information

Patent Citations

  • Carbon-coated lithium manganese iron phosphate composite material and preparation method thereof

    CN118198328A